A Consumer Experience and Luxury Brand Perception on Brand Love and Intention to Purchase - Elsa Fitriana; Meylani Tuti (University of Merdeka Malang, 2024)
The purpose of this study is to ascertain how premium brands and consumer experience affect brand loyalty and intention to repurchase. Customers of Berrybenka who have interacted more than twice make up the study's population. Purposive sampling was used in the sampling strategy, with a sample of just 200 Berrybenka product users chosen. Using smartPLS software, the data analysis method applies a structural equation model. The study's conclusions have substantial theoretical ramifications since they demonstrate the beneficial effects of luxury brands and customer experiences on brand love, as well as the importance of brand love in relation to repurchase intention. This highlights the significance of favorable encounters and opulent imagery in cultivating brand loyalty among consumers. With the help of this research, businesses may create strategies that maximize the customer experience, luxury brand, and brand love in order to boost the likelihood that customers would make repeat purchases. These tactics are essential to a company's long-term success in the fashion or luxury product industries